Dispute avoidance in New Zealand construction projects during pre-contract stage : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Construction, School of Built Environment, Massey University, Auckland, New Zealand - Silva, Weerasinghage Pramod Malaka (Massey University, 2025)
The construction industry is prone to disputes due to its complex, time-spanning and risky nature. Anywhere in the world where the construction industry is active, disputes are also prevalent, which costs the project’s objectives and good relationships among parties. New Zealand (NZ) construction industry also significantly contributes to the country’s economy and experiences disputes similar to any other country. The importance of researching the construction industry disputes has been identified, and dispute resolution, dispute avoidance and causes of disputes were highly focused. However, in the area of dispute avoidance, there has been minimal research on the possibilities during the pre-contract stage to avoid future disputes; therefore, this study has aimed at developing a pre-contract dispute avoidance toolkit for the NZ construction industry. To achieve this aim, four objectives were established namely; identification of causes of disputes, investigation of the dynamics of causes of disputes in NZ, identification of pre-contract measures to avoid potential disputes in NZ and development & and validation of a pre-contract dispute avoidance toolkit for the NZ construction industry. After the background study of previous studies in the area of construction-related disputes in international and NZ contexts, a systematic literature review on causes of disputes was carried out to identify an all-inclusive and objective list of causes of disputes. The systematic literature review identified 29 core causes of disputes, and amongst them, poor contractual arrangements, employer-initiated scope changes, and unforeseen site changes were found in most of the previous studies of causes of disputes. Then court case study on actual court cases of NZ was carried out. Based on the court case analysis, it has been concluded that the majority of disputes arose out of traditionally procured contracts, and disputant parties were mostly the principal and the contractor. Further, characteristics of causes/attributes of disputes such as significance (after considering both frequency of occurrences and level of centrality), dependencies and underlying themes were investigated. The lack of understanding of the purpose of the Construction Contracts Act was identified as the cause/attribute with the highest overall significance as well as highest centrality (a cause with the highest number of dependant causes). Considering the commonalities of the causes of disputes, five themes of causes were identified as, poor contract understanding, poor contract practices, poor contractual formation, over expectations of contractor and over expectations of principal. An attribute map illustrating the overall significances of causes/attributes linkages among attributes and themes (including attributes under themes) was also created, which provided a more organized direction and structure for the remainder of the study. Fourteen expert interviews were carried out searching for pre-contract dispute avoidance measures. 84 pre-contract measures to prevent construction-related disputes were identified under five themes. Each avoidance measure is recorded with the most responsible parties and relevant pre-contract stages. The key characteristics of these measures are clarity and communication, risk management, proper documentation and standardization, review and continuous improvements, and collaboration. Clear scope documentation and expectation management meetings were emphasized as the most important steps by respondents. Based on the gathered data from various research stages, an interactive toolkit was developed using Microsoft Power BI. The toolkit generates three outputs: dispute avoidance steps, causes/concerns of disputes, and relationships between them, based on user inputs regarding the pre-contract stage, party, and theme. Users can multi-select these inputs and explore specific dispute avoidance steps in detail, while visualizing linked causes. It underwent a two-stage validation process, including interviews and a focus group with New Zealand construction experts, leading to improvements in its functionalities and content. In general, this study has contributed to both industry practitioners and researchers by providing an innovative and interactive solution to use during the pre-contract stage of traditionally procured construction projects in NZ which is capable of avoiding potential disputes. This study recommends further exploration of the purposes of the New Zealand Construction Contracts Act's clauses. Since the study focuses on traditionally procured projects, future research could evaluate the applicability of the dispute avoidance steps to other procurement methods. It also proposes evaluating or expanding the pre-contract dispute avoidance toolkit for use in other procurement methods, with the potential to enhance it using broader data or language models to generate more accurate discussions on pre-contract dispute avoidance.
Keywords: 330202 Building construction management and project planning